Pengaruh Pendidikan Orang Tua, Pendapatan Orang Tua, dan Lingkungan Sosial Terhadap Minat Melanjutkan Perguruan Tinggi di Desa Pekadan Kecamatan Galis - Hafifah Hafifah; Ruski Ruski; Romiftahul Ulum (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study was conducted to determine the effect of parental education, parental income, and social environment on interest in continuing higher education in the village of Pekaldan, Galis District. The population of this study are children who pass and continue, those who pass do not continue and those who pass will continue using the Random Sampling technique, so that in this study a sample of 50 respondents was taken. The results of the research that has been done are known that the parental education variable has a significant effect, this is in accordance with the results of the t test, namely 5.965 > 1.678 and the significant value is 0.00 < 0.05, so it can be concluded that Ha is accepted. Parents' income variable, this is in accordance with the results of the t test, namely 5.986> 1.678 and the significant value is 0.00 <0.05, so it can be concluded that Ha is accepted. The social environment variable, this is in accordance with the results of the t test, namely 6.329 > 1.678 and the significant value is 0.00 < 0.05, so it can be concluded that Ha is accepted. The results simultaneously show that the variables of parents' education, parents' income, and social environment have a significant effect on the interest in continuing in higher education, this is in accordance with the results of the F test that is 238,689 > 7.026 and a significant value of 0.000 < 0.05, so it can be concluded that Ha accepted.